The Relevance of Law Enforcement and Human Rights in the Perception of the Indonesian Constitution - Sitompoel, Yervant T. S; Vera, Vionna Vetty; Rasji, Rasji (CV. Rayyan Dwi Bharata, 2024)
Human rights are something that humans have and are inherent in a person from birth. Human rights are fundamental rights that cannot be taken away or revoked. Human rights must also be respected, maintained and guarded by the state, law, government and everyone for honor. The relationship between human rights and the state is very close and interconnected and cannot be separated because law functions to protect human rights, apart from that, all human behavior in a country is always based on law. The constitution itself is the highest law in Indonesia and is the basis for the protection and enforcement of human rights in Indonesia. The method used in this research is a normative legal research method. In this descriptive research, the type of data used is secondary data collected through literature study, which is analyzed qualitatively, using a statutory approach. In the law there is a regulation of rights, and in human rights the legal protection is written. So the relationship between the two is related to each other and complements each other. Therefore, efforts are needed to increase public understanding and awareness of human rights and strengthen the institutions that play a role in upholding law and human rights in Indonesia. Apart from that, efforts need to be made to adopt progressive policies in advancing human rights and ensuring their protection in accordance with the constitution. Thus, it is hoped that the constitution can become an effective instrument in guaranteeing and upholding human rights in Indonesia.